Effects of Er addition and cooling rate on the corrosion resistance of Zn-5Al alloys. Issue 8 (24th May 2023) - Ge, Zhen; Huang, Chengcong; Qi, Liang; Tang, Liang; You, Shengyi
Abstract : Galfan (Zn-5Al-RE) coating is widely used in high-strength steel wires. The effects of cooling rate and the adulteration of erbium (Er) on the microstructure and corrosion resistance of Zn-5Al alloys were investigated in this study. The results show that the Zn-5Al alloy is made up of the primary η-Zn phase and eutectic structure at a high cooling rate. As the cooling rate decreases, the corrosion current firstly increased and then decreased due to decrease of the primary η-Zn content, the appearance and grew of α-Al phase. Moreover, the addition of Er leads to the formation of Er-containing intermetallic compounds in the Zn-5Al alloy, reducing the size of the primary η-Zn and α-Al phase, decreasing the corrosion current density, and improving the density and compactness of the corrosion product.